Comparison of Clinical Features between the High and Low Serum KL-6 Patients with Acute Exacerbation of Interstitial Lung Diseases. (30th November 2021) - Tagami, Yoichi; Hara, Yu; Murohashi, Kota; Nagasawa, Ryo; Nishikawa, Yurika; Tanaka, Meiro; Aoki, Ayako; Tanaka, Katsushi; Nakashima, Kentaro; Watanabe, Keisuke; Horita, Nobuyuki; Kobayashi, Nobuaki; et al.
Abstract : Background . Serum Krebs von den Lungen-6 (KL-6) measurement is widely used to assess disease activity or prognosis in patients with interstitial lung diseases (ILDs). However, the clinical differences between high and low serum KL-6 levels at the time of acute exacerbation (AE) of ILD are not well known. Methods . Clinical parameters including age, sex, Charlson Comorbidity Index score (CCIS), blood biomarkers, high-resolution CT findings, and disease mortality were retrospectively compared between high and low KL-6 (cutoff value: 1000 U/mL) patients at the time of diagnosis of AE of ILDs. Results . Thirty-eight high serum KL-6 and 57 low serum KL-6 patients were included. There was no significant difference in 6-month mortality between them (P = 0.685), whereas serum lactate dehydrogenase was a significant predictor of 6-month mortality in the high serum KL-6 patients (odds ratio (OR): 1.006; 95% confidence interval (CI): 1.003–1.009; P < 0.001), and CCIS (OR: 1.502; 95% CI: 1.242–1.838; P < 0.001) and sex (OR: 5.751; 95% CI: 1.121–105.163; P = 0.033) were significant predictors in low serum KL-6 patients. In addition, the incidences of congestive heart failure, symptomatic chronic pulmonary disease, cerebrovascular disease, and second metastatic solid tumours were significantly higher in nonsurvivors with low serum KL-6 than in other groups (P < 0.05). Conclusions . The clinical features in patients with AEs of ILDs may differ depending on the serum KL-6 level, and clinicopathological examination according to this subtyping guided by the serum KL-6 level is essential.